Nutritional composition, health benefits and bio-active compounds of chickpea (Cicer arietinum L.) - Begum, Nabila; Khan, Qudrat Ullah; Liu, Leyna G.; Li, Wenwen; Liu, Dahai; Haq, Ijaz Ul (Frontiers in Nutrition, 2023)
Chickpea (Cicer arietinum L.), an annual plant of the family Fabaceae is mainly grown in semiarid and temperate regions. Among pulses, cultivated worldwide chickpeas are considered an inexpensive and rich source of protein. Chickpea is a good source of protein and carbohydrate, fiber, and important source of essential minerals and vitamins. The quality of protein is better among other pulses. Consumption of chickpeas is related to beneficial health outcomes. Dietary peptides from the protein of chickpeas gaining more attention. Peptides can be obtained through acid, alkali, and enzymatic hydrolysis. Among all these, enzymatic hydrolysis is considered safe.Various enzymes are used for the production of peptides i.e flavorzyme, chymotrypsin, pepsin, alcalase, papain, and trypsin either alone or in combinations. Chickpea hydrolysate and peptides have various bioactivity including angiotensin 1-converting enzyme inhibition, digestive diseases, hypocholesterolemic, CVD, antioxidant activity, type 2 diabetes, anti-inflammatory, antimicrobial, and anticarcinogenic activity. This review summarizes the nutritional composition and bioactivity of hydrolysate and peptides obtained from chickpea protein. The literature shows that chickpea peptides and hydrolysate have various functional activities. But due to the limited research and technology, the sequences of peptides are unknown, due to which it is difficult to conduct the mechanism studies that how these peptides interact. Therefore, emphasis must be given to the optimization of the production of chickpea bioactive peptides, in vivo studies of chickpea bioactivity, and conducting human study trials to check the bioactivity of these peptides and hydrolysate.